PWE-236 The palatability of a savoury electrolyte drink for short bowel syndrome patients with a jejunostomy. (22nd June 2015) - Turner, P; Richman, E
Abstract : Introduction: The jejunal mucosa is permeable to sodium and consumption of low sodium fluids by patients with short bowel syndrome and jejunostomy can lead to high stoma output, sodium depletion and dehydration. The optimum solution for absorption in the jejunum contains >100 mmol/l sodium and glucose as there is coupled absorption of water sodium and glucose. 1, 2 For this reason patients are encouraged to sip around 1000 ml/day of a glucose saline solution and restrict all other fluids to <500 m/day. 3 Two preparations are commonly used: St Marks Solution (SMS) (2.5g sodium bicarbonate, 20g glucose and 3.5g sodium chloride per 1000ml water + flavour) and double strength Dioralyte (DSD) (10 sachets per 1000 mls). Patients often find these unpalatable and compliance is low often resulting in dehydration and the need for IV fluids with associated complications. Many patients also report a preference for hot drinks. Meat extracts such as Bovril contain > 100mmol/l sodium when made up as per manufacturer's instructions and the addition of glucose to these has the potential to make a savoury electrolyte solution that can be made up in small quantities and sipped while warm. Method: 1000ml of DSD and SMS were made up. Two separate 1000ml portions of Bovril were made up by adding 60g Bovril concentrate to each 1000ml hot water giving a sodium content of 100mmol/l. 20g glucose powder was added to one portion and 20g glucose polymer added to the other. The drinks were coded A-D. 8 healthy volunteers were provided with 50ml samples and asked to sip each drink. They were asked to score them out of ten for palatability, with ten being the most palatable and 0 being the least palatable. Results: Conclusion: The two savoury drinks scored highest for palatability and could therefore provide an alternative to the existing solutions. They could also be used in combination with these to give more variety and a choice of hot and cold drinks. Glucose polymer is rapidly broken down to glucose and has a theoretical advantage over glucose through being less sweet although this was not demonstrated in this small study. Further investigation of savoury electrolyte drinks in jejunostomy patients is warranted. Disclosure of interest: None Declared. References: Nightingale JMD, et al . Oral salt supplements to compensate for jejunostomy losses: comparison of sodium chloride capsules, glucose electrolyte solution, and glucose polymer electrolyte solution. Gut, 1992;33:759–761. Fordtran JS, et al . The mechanism of sodium absorption in the human small intestine. J Clin Invest 1968;47:884. Nifghtingale J, Woodward JM; On behalf of the Small Bowel Nutrition Group of the BSG. Guidelines for the management of patients with a short bowel. http://www.gut.bmjjournals.com, 2006.